Regional culture: Representations and possibilities for study - Irina Ya. Murzina (Управление культурой)
Regional cultural studies is a special scientific field that studies the features of the social, economic, cultural and political life of individual territories - has been actively developing over the past three decades. The author identifies several areas of research that are of particular relevance: Russia as a multinational unity, a multi-confessional country, Russia as a common space for the life of representatives of many peoples. The concept of "regional culture" introduced by the author - a specific form of existence of society and a person, which has a pronounced spatial and geographical outline, based on its own historical tradition and value system, producing a certain type of personality - is used in the text to characterize the processes of representation of the regional culture of the Urals. The history of the Ural culture is a vivid example of the formation and development of a regional culture. Being an integral part of the culture of Russia, at the same time, it is a relatively independent phenomenon with its own laws and logic of development. The desire to comprehend the possibilities of dialogue between regional and national cultures allows each individual to find life guidelines, and the society to realize the grounds for unity. Is the culture of the Urals provincial? The author considers the possibilities of analysis in the coordinates of "metropolitan - provincial", pointing out the distinctive features of provinciality - imitation and secondary. Today we can talk about two intersecting planes - the regional culture of the Urals (characteristics: its own historical tradition; the system of values that determines the worldview and type of personality) and the culture of the Ural region (develops in line with all-Russian and world trends, a distinctive feature is the geographical "binding" to the place of life , which does not imply a close connection with the value-semantic basis of the life of the region, and sometimes even rejects it). On the example of a general education school, the areas of local history research are highlighted - geographical, historical, linguistic, historical and cultural. As a separate discipline, schoolchildren can study the "Artistic Culture of the Urals" in the system of elective subjects of the educational program. The content of the course combines cultural, historical, cultural and art history components.